Community-Based Participatory Research Interventions to Improve Diabetes Outcomes: A Systematic Review. Issue 6 (December 2020) - Campbell, Jennifer A.; Yan, Alice; Egede, Leonard E.
Purpose: The purpose of this study was to conduct a systematic evaluation of community-based participatory research (CBPR) interventions on diabetes outcomes. Understanding of effective CBPR interventions on diabetes outcomes is limited, and findings remain unclear. Methods: A reproducible search strategy was used to identify studies testing CBPR interventions to improve diabetes outcomes, including A1C, fasting glucose, blood pressure, lipids, and quality of life. Pubmed, PsychInfo, and CINAHL were searched for articles published between 2010 and 2020. Using a CBPR continuum framework, studies were classified based on outreach, consulting, involving, collaborating, and shared leadership. Results: A total of 172 were screened, and a title search was conducted to determine eligibility. A total of 16 articles were included for synthesis. Twelve out of the 16 studies using CBPR approaches for diabetes interventions demonstrated statistically significant differences in 1 or more diabetes outcomes measured at a postintervention time point. Studies across the spectrum of CBPR demonstrated statistically significant improvements in diabetes outcomes. Conclusions: Of the 16 studies included for synthesis, 14 demonstrated statistically significant changes in A1C, fasting glucose, blood pressure, lipids, and quality of life. The majority of studies used community health workers (CHWs) to deliver interventions across group and individual settings and demonstrated significant reductions in diabetes outcomes. The evidence summarized in this review shows the pivotal role that CHWs and diabetes care and education specialists play in not only intervention delivery but also in the development of outward-facing diabetes care approaches that are person- and community-centered.